Kinerja Perusahaan Berdasarkan Pertumbuhan Investasi dan Potensi Kebangkrutan Sub Sektor Perkebunan di Bursa Efek Indonesia Periode 2014 – 2017 - Zamzami Zamzami; Osrita Hapsara; Yunan Surono (J-MAS (Jurnal Manajemen dan Sains), 2019)
This research aims to prove the stock sub group of the plantation sector has a positive value of the company (investment growth) if measured using model Tobin's q, and potential bankruptcy if measured using models Altman's Z-score first, Altman's Z-score and the Z-Altman's revision of the score as well as modifications to get the stocks that had the best performance based on the model. The sample in this study using census methods, namely the entire company group issuers shares sub plantation sector during the four-year period, starting from the observation of the year 2014-2017 recorded as many as 16 corporate issuers in Indonesia stock exchange, This form of research is research eksplanatoris. The results showed that the company's performance based on investment growth with model Tobin's q on sub plantation sector was by 20% by the year 2014, by the year 2015 amounting to 13.33% and in the year 2016 amounting to 13.33% and the year 2017 of 26.67%. Group company shares sub plantation sector which has the best performance based on the model of the Altman Z-score First for potential bankruptcy was able to note that in 2014, based on code by issuers SSMS, LSIP and AALI. In the year 2015, 2016 and 2017 which had the most improved performance is SSMS and LSIP. Group company shares sub plantation sector which has the best performance based on the model of the Altman Z-score for potential Revision of bankruptcy, it can be noted that in the year 2014, with code ANJT, LSIP issuers and SSMS. In the year 2015, 2016 and 2017 which had the most improved performance is LSIP. Group company shares sub plantation sector which has the best performance based on the model of the Altman Z-score for potential bankruptcy Modification is the year 2014, with code issuers LSIP, SSMS, ANJT, AALI, SGRO and GOLL. In the year 2015, the stocks that have the most excellent performance namely LSIP, ANJT, AALI and SSMS. In the year 2016, the stocks that have the most excellent performance namely LSIP, AALI, ANJT, PALM, SSMS, SMAR and SIMP and the year 2017 which had the most improved performance is LSIP, AALI, ANJT, SSMS and SMAR.